Mucin Production Correlates with Dual Expression of Epidermal Growth Factor Receptor and Its Ligand the Epidermal Growth Factor in Non-Small Cell Lung Cancer - Rancés Blanco; Charles E Rengifo; Elizabeth Domínguez; Damián Blanco; Mercedes Cedeño; Enrique Rengifo (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Introduction: Mucoproduction plays an important role in the processes of tumor progression, invasion and metastasis. In non-small cell lung cancer (NSCLC), mucins hypersecretion has been associated with alterations in the epidermal growth factor receptor (EGFR) expression. However, the relation of mucins with EGFR in these tumors is not completely clarified. Aims: To evaluate the relation between mucoproduction, the expression of EGFR and its  ligand the epidermal growth factor (EGF) in NSCLC samples. Materials  and  Methods: A number of 71  routinely  processed  formalin-fixed  and paraffin-embedded archival samples with diagnosis of NSCLC were used. Mucoproduction was considered when periodic acid-Schiff reaction (PAS) positive and/or alcian blue positive substances were observed. The immunolocalization of EGFR and EGF molecules were detected by mean of immunohistochemical methods. Chi-square test was applied to compare two or three different parameters. In all cases, the criterion for statistical significance was p<0.05. Results: The production of mucins was related with the occurrence of metastasis (p = 0.0151) as well as, with a more advanced stage of NSCLC disease (p = 0.0409). The presence of mucin was statistically significant associated to histology (p < 0.0001) and degree of cytological atypia (p = 0.0325). The expression of  EGFR  was  associated with mucin  hyperproduction  (p  =  0.0205). The  levels of mucin production  was statistical  significant  increase  in  NSCLC  samples  displaying  double  expression  of  EGFR  and  EGF (p=0.0297) when compared with EGFR-/EGF+ and EGFR-/EGF-. Conclusions: The  results  obtained  in  the  present  work  could  support  the  role  of uncontrolled  EGFR system activation mediated by the ligand EGF in NSCLC mucins hyperproduction as well as its relation with tumor progression and metastasis processes.